Effect of Emotional Intelligence, Commitment, and Motivation Towards Lecturer Performance - Mukti Ali; Munir Sukoco; Falih Suaedi (LPPM of NAROTAMA UNIVERSITY, 2018)
Purpose: Make a document key performance indicator associated with emotional intelligence, commitment, and motivation on the performance lecturer at the Universitas Maarif Hasyim Latif Sidoarjo. Design/methodology/approach: The research uses quantitative methods to the associative and using regression analysis techniques and equational structure modeling for determining hypothesis. Findings: The research was based on the findings of non-optimal lecturers performance in carrying out the task, they allegedly a violation of labor discipline, still high levels of absenteeism and tardiness in teaching. Research limitations/implications: Predicting the magnitude of the variation, form relationships and determine the direction and magnitude of effect between the independent variables with the dependent variable. Practical implications: Can document the whole process of planning and strategic steps in efforts to implement the increase in faculty performance through increased emotional intelligence, commitment, and motivation on the performance of a lecturer at the Universitas Maarif Hasyim Latif Sidoarjo. Originality/value: An input for policy making in the improvement and development of the organization and management of universities, in particular, relating to the development Lecturer performance through the development of emotional intelligence, commitment, and motivation more. Paper type: Research paper.